2017
DOI: 10.1080/17429145.2017.1283069
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and spatial pattern of predominant tree species in a pine–oak mosaic mixed forest in the Qinling Mountains, China

Abstract: This study investigated a typical pine-oak mosaic mixed forest in the Qinling Mountains, China. In the sample plot, the population structure and spatial distribution of the stems were analyzed for the predominant species, to identify the mechanisms of species coexistence and successional trends of the forest. The population structures of all species were bimodally distributed, with young trees (DBH <1 cm) more abundant than older trees. The population structures of Quercus aliena var. acuteserrata was bimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
3
6
1
2
Order By: Relevance
“…Across the study sites, the range of total basal area cover varies from 16.48 to 35.3 m 2 ha -1 and the total tree density from 276 to 868 trees ha -1 were comparable to the temperate pine-Oak mixed forest of Qinling mountains in north-western China [85], tropical forest of Kenya [86] and fragmented Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 6 August 2020 doi:10.20944/preprints202008.0136.v1…”
Section: Community Charactersticsmentioning
confidence: 84%
“…Across the study sites, the range of total basal area cover varies from 16.48 to 35.3 m 2 ha -1 and the total tree density from 276 to 868 trees ha -1 were comparable to the temperate pine-Oak mixed forest of Qinling mountains in north-western China [85], tropical forest of Kenya [86] and fragmented Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 6 August 2020 doi:10.20944/preprints202008.0136.v1…”
Section: Community Charactersticsmentioning
confidence: 84%
“…The reciprocal relationship between rodents and plants community varies in different forest habitat, it is particularly important to understand the role of scatterhoarding animals in plant inter-community competition. Forest community junction is considered a unique environment, it is an area where the competition between plant communities is most prominent (Kang et al 2017) and animal activity is more frequent because of the greater diversity and abundance of food resources (Yu et al 2018). Many previous studies have investigated the ecological process, stand development dynamic and population characteristics of plant community junction (Gracia et al 2002;Mendes et al 2016;Kang et al 2017), whereas few have considered the relationships among animals and plant community competition according to their foraging behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mixed forests exhibit high species richness and distinctive species compositions, and they have essential roles in maintaining biodiversity and ecosystem functions (Stone 2006). Previous studies have indicated that competition gradually increases with the development of populations in the edge between pine and oak forests, where Pinus species are considered to be the pioneer species during succession and they are usually invaded by late successional Quercus species (Gracia et al 2002;Yu et al 2014;Kang et al 2017). However, the mechanism responsible for driving the invasion process is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os padrões de distribuição espacial das plantas diferem-se com base em diversos processos e dinâmicas, como competição intra e interespecífica, além de perturbação ou heterogeneidade ambiental e dispersão de sementes -bastante dependentes da fauna e da ocorrência e frequência de ventos (Kang et al, 2017). A ação destes agentes pode determinar os três diferentes padrões de distribuição: agregado, aleatório e uniforme (Townsend et al, 2010).…”
Section: Introductionunclassified